Acquisition of English tense and agreement morphology by L1 Malay and L1 Chinese speakers - Wong, Bee Eng (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper reports on a study that investigates the acquisition of English tense and agreement morphology by Malaysian ESL (English as a Second Language) learners. These learners speak Malay and Chinese. In other words, they are Malaysian L1 Malay and L1 Chinese speakers of L2 English. The Failed Functional Features Hypothesis (Hawkins and Chan, 1997) serves as the framework for the study. The hypothesis claims that post-childhood second language (L2) learners experience syntactic deficits in the L2 if parameterised features present in the functional categories of the L2 are not specified in the L1. However, selected L1 features that correspond to L2 settings are able to enter L2 syntactic derivations. In terms of form-meaning relationships, it is predicted that a syntactic deficit resulting from an L1 influence will affect the assignment of native-like meanings to surface forms. And depending on the differences in the L1 and L2, learners from different L1 backgrounds will not show similar patterns of development. The study gathered data from the two groups of ESL learners in an attempt to compare the role played by the Chinese and Malay languages in the acquisition of the English property being investigated. A grammaticality judgement task (comprising both grammatical and ungrammatical items) was designed to test the learners’ underlying knowledge of tense and agreement morphology in English. The task comprised 16 correctly inflected items with thematic and copula/auxiliary be verb forms, and 32 incorrectly inflected items. The findings suggest that apparent near native-like acquisition of the L2 property might not be the case when learners seem to have more difficulty with the ungrammatical items than the grammatical items. The findings of this study have pedagogical implications for the ESL (English as a Second Language) classroom.